PERUBAHAN SOSIAL-BUDAYA PETANI ORGANIK DI YOGYAKARTA - Zamroni, Muhammad Imam (P2KK LIPI, 2010)
Since 1960s the government implemented Green Revolution policy to develop Indonesian agricultural sector due to the food crisis and the concern population growth that had reached 2.5 percent and to accelerate rural development. The introduction of agricultural technology and the use of chemical fertilizer, pesticide and herbicide, become the main program of the government to increase agricultural productivity and the welfare of farmer’s life, but they had caused damage in the long run. The impact of high level use chemical fertilizers and pesticides for several decades, have reduced soil fertility, damage soil structure and organic content. To reverse the situation, the farmers in the village Seruthave tried to introduce a model of agriculture which is environment-friendly and set out a sustainability model called organic farming or integrated farming. The transition from conventional farming into organic farming has changed of social-cultural behavior of the community and increased social welfare in Serut. This article aims to discuss socialcultural and behavioral changes among organic farmers in the sub-village Serut, Palbapang village, Bantuldistrict, Yogyakarta province. The methods of data collection were indepth interview, direct observation and documents analysis. Keywords: organic farming, social-cultural change, social welfare